STUDIES ON THE COMPONENT APPROACH OF SELECTION IN BLACK GRAM [Vigna mungo (L.) HEPPER] - MUNAGALA SAI KIRAN; G. M. LAL (The Bioscan, 2021)
The present investigation on variability, correlation, and path coefficient analysis for yield and yield attributing traits was conducted as a field experiment comprising 25 genotypes of black gram [Vigna mungo (L.) Hepper] during Kharif-2019. Among these characters Highest GCV and PCV and high estimates of heritability were recorded for the character number of pods per plant and number of pods per cluster (rg=0.579**, rp= 0.405**), number of seeds per pod (rg=0.369**, rp=0.410**), and biological yield (rg= 0.776**, rp= 0.613**) are highly significant and positively correlated with seed yield at both genotypic and phenotypic level. The highest positive direct effect on seed yield was recorded for plant height (0.8259) followed by harvest index (0.7132), number of pods per plant (0.6054), number of primary branches per plant (0.5908), days to maturity (0.5638), and biological yield (0.1975) at the genotypic level. While at the phenotypic level high positive direct effects were observed for harvest index (0.9518) followed by biological yield (0.2201), the number of clusters per plant (0.0583), days to maturity (0.0392), number pods per cluster (0.0317) and pod length (0.0215). Selections of these traits are expected to lead to positive results in the improvement of seed yield in the characters studied.